2013
DOI: 10.1155/2013/676190
|View full text |Cite
|
Sign up to set email alerts
|

Safety Analysis Using Lebesgue Strain Measure of Thick‐Walled Cylinder for Functionally Graded Material under Internal and External Pressure

Abstract: Safety analysis has been done for thick-walled circular cylinder under internal and external pressure using transition theory which is based on the concept of generalized principal Lebesgue strain measure. Results have been analyzed theoretically and discussed numerically. From the analysis, it can be concluded that circular cylinder made of functionally graded material is on the safer side of the design as compared to homogeneous cylinder with internal and external pressure, which leads to the idea of “stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…This theory has been applied to many problems; for example, Sharma et al [ 11 ] analyzed thermal elastic-plastic stresses in transversely isotropic thick-walled rotating cylinder under internal pressure. Aggarwal et al [ 12 ] investigated safety factors in thick-walled functionally graded cylinder under internal and external pressure and concluded that functionally graded cylinder is a better choice for designers as compared to cylinders made up of homogeneous materials. Aggarwal et al [ 13 ] discussed safety factors in creep nonhomogeneous thick-walled circular cylinder under internal and external pressure with steady state temperature and concluded that cylinder made up of nonhomogeneous material is better choice for designing as compared to cylinder made up of homogeneous material.…”
Section: Introductionmentioning
confidence: 99%
“…This theory has been applied to many problems; for example, Sharma et al [ 11 ] analyzed thermal elastic-plastic stresses in transversely isotropic thick-walled rotating cylinder under internal pressure. Aggarwal et al [ 12 ] investigated safety factors in thick-walled functionally graded cylinder under internal and external pressure and concluded that functionally graded cylinder is a better choice for designers as compared to cylinders made up of homogeneous materials. Aggarwal et al [ 13 ] discussed safety factors in creep nonhomogeneous thick-walled circular cylinder under internal and external pressure with steady state temperature and concluded that cylinder made up of nonhomogeneous material is better choice for designing as compared to cylinder made up of homogeneous material.…”
Section: Introductionmentioning
confidence: 99%
“…They observed that the radial stress in the cylinder decreases throughout with the increase in reinforcement gradient, whereas the tangential, axial, and effective stresses increase significantly near the inner radius but show significant decrease towards the outer radius. Aggarwal et al [10] investigated safety factors in terms of elastic-plastic stresses for functionally graded thickwalled circular cylinder under internal and external pressure and concluded that functionally graded thick-walled cylinder minimizes the possibility of fracture of the cylinder. Aggarwal et al [11] calculated thermal creep stresses for nonhomogeneous thick-walled cylinder under internal and external pressure using Lebesgue strain measure and concluded that nonhomogeneous cylinder is better choice of design as compared to homogeneous cylinder.…”
Section: Introductionmentioning
confidence: 99%